Austerity, Welfare and Work : Exploring Politics, Geographies and Inequalities - Etherington, David (Staffordshire University) (Book collections on Project MUSE., 2020)
The impacts of austerity and welfare reform on work and employment relations are explored in this perceptive assessment. This book highlights the role of trade unions and social movements in challenging the insecurities and inequalities imposed by work-focused welfare policies such as Universal Credit and proposes progressive new paths for welfare.